Revisão de métodos de correção de fator de potência e projeto de um conversor boost PFC - Guerra, Antônio Luiz (2021)
Improving the conscious use of energy and its efficiency, the work proposes a resolution of how powers are dissipated in loads in alternating current and how the power factor can be applied to increase the efficiency of a system, taking into account passive and active techniques correction of this factor. Industrial applications and single-phase rectifiers will be analyzed, with the last example being the implementation via simulation of a convert Boost PFC with UC3854 controller. Practical results obtained through the commercial development board STEVAL-ISA102V2 are also presented, controlled by the L6562A analog controller, and compared with the values presented by the manufacturer and by the simulation with the UC3854 controller, thus showing the development of the technology in factor correction power.